Can Tall Guinea‐Race Sorghum Hybrids Deliver Yield Advantage to Smallholder Farmers in West and Central Africa?. Issue 2 (2nd February 2017) - Kante, Moctar; Rattunde, Henry Frederick W.; Leiser, Willmar L.; Nebié, Baloua; Diallo, Bocar; Diallo, Abdoulaye; Touré, Abocar Oumar; Weltzien, Eva; Haussmann, Bettina I.G.
Abstract : Many farmers in West and Central Africa (WCA) prefer tall (>3 m) grain sorghum [ Sorghum bicolor (L.) Moench] for various reasons. This study seeks to determine (i) what yield superiority newly bred, tall, photoperiod‐sensitive guinea‐race sorghum hybrids can provide relative to an adapted landrace variety across a wide range of productivity conditions, and (ii) the risk of these hybrids failing to provide yield superiority for individual farmers. Seven hybrids, one local check, and eight pure‐line progenies were evaluated in 37 farmer‐managed, on‐farm yield trials across three Malian zones and 3 yr. Environments were classified into four productivity groups (low [0.78–1.10 Mg ha −1 ], mid‐low [1.10–1.50 Mg ha −1 ], mid‐high [1.50–2.00 Mg ha −1 ] and high [2.00–2.65 Mg ha −1 ]) based on their trial mean grain yield. Mean yields of the seven tall hybrids were 3 to 17% (ranging from 0.06 to 0.28 Mg ha −1 ) higher than that of the local check across all environments and were highest (14–47%) averaged across the seven trials with the lowest mean yields. The individual overall highest‐yielding hybrid showed superiorities over the local check in the low, mid‐low, mid‐high, and high productivity levels of 0.43 (47%), 0.14 (10%), 0.47 (27%), and 0.34 (14%) Mg ha −1, respectively. The tall hybrids rarely had yields significantly inferior to the local check. Farmers' preference for, and the possible benefits of, taller plant types may lead farmers to grow tall hybrids, particularly under the typical low‐productivity production conditions of WCA.